How Long Does (S)He Have? Retrospective Analysis of Outcomes After Palliative Extubation in Elderly, Chronically Critically Ill Patients. Issue 6 (June 2016) - Pan, Cynthia X.; Platis, Dimitris; Maw, Min Min; Morris, Jane; Pollack, Simcha; Kawai, Fernando
Abstract : Objective: For chronically critically ill elderly patients on mechanical ventilation, prognosis for significant recovery may be minimal. These individuals, or their surrogates, may decide for "palliative extubation." A common prognostic question arises: "How long does she/he have?" This study describes demographics, mortality, time to death, and factors associated with death after palliative extubation. Design, Setting, and Patients: Retrospective 3-year study in community hospital with ethnically diverse elderly population. Chronically critically ill patients followed from palliative extubation to death or survival to discharge. Measures: Mortality/survival following palliative extubation, time to death or discharge, factors associated with death. Results: Hundred and forty-eight subjects underwent palliative extubation. Mean age: 78 years, 60% female, ethnically diverse with 46% white, and 54% others. Top diagnostic categories: sepsis (47%) and respiratory failure (22%). After extubation, 114 patients (77%) died in hospital and 34 (23%) were discharged. Of those who died, median time to death 8.9 hours (range, 4 min to 7 d). Mortality proportion was 56% at 24 hours and increased with time. Factors associated with early death: Systolic blood pressure less than 90 ( p = 0.002) and Charlson Comorbidity Index that is above 6 or 0 ( p = 0.002). Conclusions: Palliative extubation at end of life was an option selected by an ethnically diverse elderly population. Approximately three-fourths of subjects died in hospital, and one-fourth was discharged alive. Over 50% who died did so within 24 hours, making this useful information for counseling and anticipatory planning. Subjects with systolic blood pressure less than 90 and Charlson Comorbidity Index that is very low or very high had higher mortality.